EVALUASI PELAKSANAAN PROGRAM TAMAN BACAAN MASYARAKAT (TBM) TALENTA AZZURA DI JOGOYUDAN, JETIS, KOTA YOGYAKARTA - Tony Sunaryanta (Perspektif Ilmu Pendidikan, 2007)
This article is an evaluation result of the program implementation of TBM â€œTalenta Azzuraâ€ at Jogoyudan, Jetis, Jogyakarta. The evaluation was aimed at (1) communityâ€™s interest on the program, (2) community as members, (3) managers and attendants, (4) support systems, (5) fund, (6) management systems, (7) services, and (8) usefulness either for its members or the community. Subjects of the evaluation were members as well as the managers and staffs of TBM â€œTalenta Azzuraâ€. Data were gathered through techniques of observation, interviews, questionnaires, and documentation. The analysis was conducted by using SPSS 10,00 for Window (statistical program), it was descriptive. The Evaluation model applied was Stufflebeamâ€™s CIPP (context, inputs, process, and product). The evaluation results indicate that community has diversed socio-economic background as shown by the total income of parents ranges from Rp. 500.000,- to Rp. 750.000,-/month. Most membersâ€™ parents are vendors. The questionnaires drew a conclusion that communityâ€™s support quality is mediocre yet no rejection or feelings against the program. Further, conclusions drawn upon evaluation model are (1) inputs are members who age between 3 â€“ 12 years old, mostly higlymotivated girls, (2) there are two categories of the managers and staffs, permanent managers or attendants are from the community itself and there are some part-time attendants. Somehow the TBM gets little support for services and lack of fund. Results from questionnaires regarding process show low quality of management and services though data gathered regarding mentoring program indicate meaningfulness of the program for members and the community. In regards of product, results from questionnaires,interviews and observation picture that the existence of TBM is advantageous either for members or the community.